GROWTH AND YIELD OF THREE VARIETIES OF MAIZE IN DRY LAND AT WAIHATU VILLAGE, WEST PART CERAM REGENCY - MP Sirappa; A.J. Rieuwpassa (Agros Journal of Agriculture Science, 2013)
Activity was conducted in July until October 2009. Research prepared on randomized block design, three replications. Purpose: to know respons of three maize varieties which cultivated on dry land. Size of plots area is 15 m × 16 m, plant spacing 75 cm × 40 cm, two plants per hole. Varieties assess is Bima-3 Bantimurung, Srikandi Kuning, and Bisi-2. Dosage of fertilizer used is NPK Phonska 300 kg, urea 300 kg, chicken manure two t ha-1. Study shows: varieties Bima-3 Bantimurung, Srikandi Kuning give highest growth and yield than Bisi-2. Phonska NPK fertilizer application combined with manure give average yield of maize is higher than average of national and Moluccas yields, each 3.45 t ha-1 and 2.30 t ha-1, respectively. Bima-3 Bantimurung hybrid variety gives average highest yield and not significantly different from composite Srikandi Kuning, but significantly different from hybrid Bisi-2. Bima-3 Bantimurung and Srikandi Kuning potentially developed on dry land in Moluccas because in addition to high yield, Bima 3 Bantimurung a maize hybrid that has a high biomass and stay green until harvest so that waste can be utilized for animal feed, while Srikandi Kuning is a composite maize rich of protein that can be used as an alternative food sources. Key-words: growth, variety, maize.